Audit Report Lag: Peran Key Audit Matters, Karakteristik Firma Audit, dan Faktor Lainnya - Aulia Fasha Julianti; Dewi Kurnia Indrastuti (Media Bisnis, 2026)
The purpose of this study is to examine empirically how important key audit matters, audit firm characteristics, and other variables affect audit report lag. The independent variables employed in this study include profitability, firm size, auditor specialization, key audit matters, audit opinion, and public accounting firm, while audit report lag is used as the dependent variable. The object of this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. A purposive sampling method was used in selecting the research sample, resulting in 225 companies with a total of 675 firm-year observations that met the research criteria. Using multiple linear regression analysis, the data were examined. The results of this study indicate that profitability, audit opinion, and public accounting firms have a negative effect on audit report lag because higher profitability encourages timely financial reporting, companies that receive an unqualified audit opinion face fewer material issues so that the audit can be completed without extended procedures, and companies audited by Big Four public accounting firms benefit from more efficient audit resources and methodologies. Meanwhile, firm size, auditor specialist, and key audit matters are found to have no significant effect on audit report lag.